Evaluasi Program Posyandu Lanjut Usia di Kecamatan Mawasangka Kabupaten Buton Tnegah - Fazriani; Herman H; Novayanti Sophia Rukmana S (Universitas Negeri Makassar, 2025)
This study aims to determine the implementation of the Elderly Posyandu Program and the evaluation results of the implementation of the Elderly Posyandu Program in Mawasangka District, Central Buton Regency types of qualitative descriptive research. Data collection techniques are done through observation, interviews, and documentation. Data analysis techniques include data collection, condensation, presentation, and conclusions drawn. The results of the study show that the input aspect of the availability of health workers in both villages is quite adequate, with 1 Doctor, 2 Midwives, and 5 Cadres. However, there is a significant obstacle in the form of limited funds, with the APBDes budget of only Rp 150,000 per month, which hinders the provision of compensation for cadres and the procurement of adequate medical equipment. Some medical equipment is often out of stock, disrupting the smooth running of routine checkups for older people. Process Coordination between health centres, cadres, and village governments is going well, but there is unevenness in health services. In Napa Village, additional examinations are carried out regularly, while in Wakambangura II Village, there is no healthy gymnastics program for older people, and follow-up examinations are rarely carried out. Solid scheduling and effective coordination help the program run smoothly, although sometimes schedule changes due to external factors cause obstacles. Output The difference in the type of service between the two villages significantly impacts the participation rate of older people. Napa Village has a higher participation rate, reaching around 80 people, thanks to additional activities such as elderly gymnastics and follow-up examinations. Meanwhile, Wakambangura II Village only reaches 64 people, although the ideal target is 70-80%. Outcome The positive impact on older people's physical and mental health is seen as more significant in Napa Village. On the other hand, in Wakambangura II Village, older people's awareness of the importance of routine health check-ups is still low, and access to health services is limited, especially for older people who live far from the Posyandu centre. The recommendations of this study are (1) Increasing the budget to support operational activities and procurement of medical equipment, (2) Implementing routine healthy gymnastics for older people in Wakambangura II Village, (3) Increasing awareness of older people in Wakambangura II Village regarding the importance of routine health check-ups (4) Improving access to health services for older people who live in remote areas.